Multi-Regime Law Enforcement of Transnational Organized Fisheries Crime: A Comparative Study of Indonesia and Australia - Maya Shafira; Andre Arya Pratama; Ahmad Irzal Fardiansyah; Shofriya Qonitatin Abidah (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
The context of law enforcement on IUU Fishing can’t be separated from including other criminal acts as part of organized transnational fisheries crime in Indonesian waters. Multi-regime criminal activities are evident in the Case of the Run Zheng 03 and 05 Ships, which were detected carrying out illegal fishing and the Crime of Human Trafficking (TPPO) against Indonesian crew members in the Arafura Sea. Unfortunately, Articles 92 and 93 Paragraph 2 of the Fisheries Law, as well as the ratification of the Agreement on Port State Measures to Prevent, Deter, and Eliminate Illegal, Unreported, and Unregulated Fishing (PSMA) which are regulated in executive regulations, have found obstacles that are still systemic so that crimes in the context of fishing still require high-level supervision. Therefore, this problem must be overcome by conducting a comparative study with Australia, a best practice country that has also ratified PSMA, like Indonesia. This study uses a normative legal method, referring to applicable laws and regulations related to the case phenomenon. A comparative study also accompanies the research as a best practice in finding solutions to legal problems that can be seen in other countries. The results of the study show that the existing conditions show a lack of coordination system and capacity between ministries or institutions, such as between the Ministry of Transportation and the Ministry of Marine Affairs and Fisheries in joint supervision with law enforcement officers, and the designated ports are still unable to optimize fishing vessels entering the port. The information system between countries is still integrated manually. The threat of imposing criminal penalties on corporations as a paradigm for punishment and accommodating PSMA in technical provisions is also evidence of the government's lack of firmness in eradicating fisheries crimes. Thus, Australia can be an example of its efforts as a member of IUU Fishing by accommodating PSMA into the Fisheries Management Act, and the systematization of coordination between AFMA and the Australian Maritime Security Operations Center is running well without any coordination problems or overlapping authorities.